Analisis Likuiditas, Leverage dan Ukuran Perusahaan - Dicky Perwira Ompusunggu; Sapna Rahayu (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Research to better understand the real estate and plantation market in Indonesia, analyze the factors that affect returns on investment, and make policy recommendations that can improve efficiency and productivity in these areas. Combined quantitative research was conducted to investigate liquidity, leverage, and company size to determine the relationship between these variables. One factor that affects a business's value is its profitability, which can be measured from the profits generated by the company every year. If the company is very productive and profits increase, it will attract investors, and the value of the company will grow. Profitability is the ability to generate profits from sales or investments, while liquidity is the ability to pay short-term obligations on time. Leverage measures how well a company uses debt to finance its operations, and company size is the company's total market value.